Risk Factors for Endometriosis in a German Case–Control Study - Burghaus, S.; Klingsiek, P.; Fasching, P. A.; Engel, A.; Häberle, L.; Strissel, P. L.; Schmidt, M.; Jonas, K.; Strehl, J. D.; Hartmann, A.; Lermann, J.; Boosz, A.; Thiel, F. C.; Müller, A.; Beckmann, M. W.; Renner, S. P. (Geburtshilfe und Frauenheilkunde, 2011)
Objective: The etiology of endometriosis is still a research field in which few consistent data are available. Large case–control studies or even cohort studies are rare, and most of the published data are conflicting. The aim of the present study was therefore to examine common epidemiological and endometriosis-specific risk factors in a German case–control study. Design: From 2001 to 2010, a pool of 595 laparoscopically confirmed cases and 475 controls were recruited in a hospital-based setting. After matching for age, 298 cases and 300 controls remained in the pool. Age at menarche, menstrual cycle length, duration of menstrual bleeding, number of pregnancies, live births, miscarriages, use of contraceptive pills, body mass index (BMI), and smoking status were analyzed with logistic regression models predicting endometriosis case–control status. Results: Menstrual cycle length, duration of menstrual bleeding, number of pregnancies, number of miscarriages, and smoking status, as relevant predictors for endometriosis case–control status, were identified as risk factors for endometriosis. Other factors such as age at menarche, number of live births, ever having used contraceptive pills, and BMI were not predictive. Conclusions: This hospital-based case–control study reproduced most of the familiar risk factors. Comparison of this study with others reveals a wide variety of effect sizes and directions of association with risk factors and may increase the information available about the characteristics of the patient population being treated in the relevant hospital setting.
Keywords: endometriosis; risk factor; case-control study; epidemiology; genetics